A new species of Psacalium (Asteraceae, Senecioneae) from the state of Guerrero, Mexico - Villaseñor, José Luis; Hinojosa, Oscar; Redonda-Martínez, Rosario (Phytotaxa, 2018)
Psacalium villosum is described from the central mountainous region of the state of Guerrero, Mexico. This novelty belongs to the peltate group of Psacalium and is distinguished primarily by its densely villose capitulescence axis and branches. In addition, the capitulescence lacks bracts. The heads are obscurely calyculate, bear up to 44 florets, and have a glandular-stipitate receptacle. Here, we describe and illustrate this new species. We also provide a distribution map and a comparison with similar taxa.